State of perinatal mental health care in the WHO region of Europe: a scoping review - Horakova, Anna; Nemcova, Hana; Hrdlickova, Kristyna; Kalli, Stefani; Davletova, Alina; Duarte, Mario Filipe Rodrigues Saraiva; Molodina, Darya; Riekki, Tiina; Sebela, Antonin (Frontiers in Psychiatry, 2024)
Background: Although perinatal mental disorders are the most common health complication among women in the perinatal period, there is a huge gap in the implementation of related research findings in the health care system. We mapped the state of perinatal mental health (PMH) care in the WHO Europe region with aim to identify leading countries, which can serve as models for countries with less developed perinatal mental health care. Methods: Guidelines, policies, and documents related to screening and treatment services for PMH were searched as grey literature. Results were analysed to assess the status of PMH care in the WHO European countries and to identify gaps (absence of relevant service or documents). The state of perinatal mental health care was scored on a 0-5 scale. Results: The grey literature search resulted in a total of 361 websites. Seven countries (Belgium, Finland, Ireland, Netherlands, Sweden, UK, Malta) received full points for the presence of relevant PMH services or documents, while five countries received zero points. Most WHO European countries (48/53) have general mental health policies, but only 25 countries have policies specifically on perinatal mental health. Ten countries offer PMH screening, and 11 countries offer PMH service (of any type). Any PMH guidelines were provided in 23/53 countries. Conclusion: Perinatal mental health care is in its infancy in most WHO European countries. Leading countries (Belgium, Finland, Ireland, Netherlands, Sweden, UK, Malta) in PMH care can serve as conceptual models for those less developed and geopolitically close.